The state of the art in anti-aging: plant-based phytochemicals for skin care - Merve Tomas; Deniz Günal-Köroğlu; Senem Kamiloglu; Tugba Ozdal; Esra Capanoglu (Immunity & Ageing)
Abstract Phytochemicals help mitigate skin aging by scavenging free radicals, modulating key enzymatic pathways, and promoting the skin’s structural integrity. Carotenoids, vitamins, essential fatty acids, and phenolic compounds work by acting as antioxidants, inhibiting enzymes like hyaluronidase, collagenase, and elastase, which degrade skin structure, and reducing levels of inflammatory markers (IL-6, IL-8, etc.) and matrix metalloproteinases (MMP-1, MMP-2) linked to aging. Recent research highlights that plant-based phytochemicals can improve skin elasticity, reduce hyperpigmentation, prevent the breakdown of important skin proteins, and support wound healing, making them valuable components for skin care and treatments. This review explores the multifaceted roles of phytochemicals in maintaining and improving skin health, highlighting their mechanisms of action and potential in skin anti-aging innovations.